2010
DOI: 10.1007/s10669-010-9292-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of gas flaring in the rapid corrosion of zinc roofs in the Niger Delta Region of Nigeria

Abstract: This study examined the role of gas flaring in the rapid corrosion of zinc roofs in the Niger Delta Region of Nigeria. Four experimental sites were set up where samples of galvanized iron sheet (popularly called ''zinc roofs'') were exposed to the atmosphere. The corrosion behaviour of galvanized iron sheet through weight loss determination under different environmental conditions was monitored. A uniform angle of inclination of 22°( which represents the mean angle of inclination of house roofs in the study ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 11 publications
(8 reference statements)
1
31
0
Order By: Relevance
“…8) revealed that Rivers State was at the greatest risk of acid deposition, followed by Akwa Ibom. This corroborates previous studies, where rainwater was found to be acidic around flaring locations (Ovri and Iroh, 2013;Ekpoh and Obia, 2010;Nduka et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…8) revealed that Rivers State was at the greatest risk of acid deposition, followed by Akwa Ibom. This corroborates previous studies, where rainwater was found to be acidic around flaring locations (Ovri and Iroh, 2013;Ekpoh and Obia, 2010;Nduka et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…As the evaporation of the volatile lower molecular weight components affect aerial life, so the dissolution of the less volatile components with the resulting emulsified water, affects aquatic life. On the other hand, Gas flaring is the burning or disposing of waste gases through the use of combustion [22]. Most of the gas flaring that occurs in the Niger Delta region is around oil wells that are close to farmlands and dwelling homes.…”
Section: The Concept Of Environmental Degradationmentioning
confidence: 99%
“…Apart from being state headquarters, the cities where this study was conducted, are also centres of intense developmental activities involving building construction. It has to be noted that Nigerian economy is primarily dependent on hydrocarbon oil that is extracted mainly from this region (Ekpoh & Obia, 2010). The huge investment in the oil sub-sector has led to high influx of people and industries into the region, leading to massive housing development.…”
Section: Study Areamentioning
confidence: 99%